Preoperative patient teaching practices and associated factors among nurses working at hospitals in West Shoa Zone, Ethiopia, 2022: a cross-sectional study - Atomsa, Lammi; Temesgen, Sidise; Dechasa, Abebe; Ayana, Mulatu; Amena, Nimona; Teklehymanot, Dawit; Regea, Firaol (Frontiers in Public Health, 2024)
IntroductionPreoperative teaching is fundamental nursing activity in which a nurse educates the patient about surgery and what to anticipate following the procedure. It is a process via which nurses give standard preoperative information to patients before surgery, and it enables the patients to understand their diagnosis and treatment, actively participate in their own care, overcome feelings of incapacity in relation to their condition, regain health, and maintain home care. However, there is a dearth of studies that determine the extent of preoperative teaching practice in Ethiopia in general and in the study area in particular.ObjectiveThis study aimed to assess preoperative patient teaching practices and the factors associated with these practices among nurses working in hospitals in the West Shoa, Oromia region, Ethiopia, in 2022.MethodsAn institution-based cross-sectional study was conducted among 267 nurses from 1 September to 30 September 2022, at hospitals in the West Shoa Zone. Two-stage simple random sampling technique was used to select study participants. Data were collected using a pretested and structured self-administered questionnaire. The quantitative data were checked and entered using Epi-data version 4.6 and exported to SPSS version 26.0 for analysis. Bivariable and multivariable logistic analyses were performed, and p-values of <0.05 at a 95% confidence interval were considered statistically significant.ResultA total of 253 nurses returned the entire questionnaire, yielding a response rate of 94.75%. The study enrolled 132 (52.2%) male, the highest percentage (231, 91.3%) of the participants were in the age group of 18–35, the majority of participants (152, 60.1%) were married, and 164 (64.8%) were protestant. Approximately 101 (39.9%) participants demonstrated good preoperative teaching practice. Lack of teaching material, lack of training workload, time constraints, insufficient staffing, language barrier, severity of patient cases, patient and family’s anxiety, and complexity of patients’ status were significantly associated with preoperative patient teaching practice.ConclusionThe proportion of preoperative patient teaching practices among nurses working at hospitals in the West Shoa Zone was low. Concerned bodies should emphasize ways to improve preoperative teaching practice.